1998
DOI: 10.1034/j.1600-0412.1998.770309.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pregnancy is not associated with obstructed labor, A study among Pakistani women in Karachi

Abstract: Vitamin D deficiency in pregnancy is common in Karachi, but is not associated with mechanical dystocia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…While they did not examine the indications for cesarean, a small case-control study of Pakistani women looked at a specific cause (cesarean for obstructed labor from cephalopelvic disproportion) but reported no association with 25(OH)D at delivery [6]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While they did not examine the indications for cesarean, a small case-control study of Pakistani women looked at a specific cause (cesarean for obstructed labor from cephalopelvic disproportion) but reported no association with 25(OH)D at delivery [6]. …”
Section: Discussionmentioning
confidence: 99%
“…A Cesarean may be performed for reasons related to the mother or to the fetus including prolonged labor (dystocia), fetal distress, fetal malpresentation or a prior cesarean delivery [2]. Factors which increase risk include older maternal age, obesity, parity and ethnicity [3,4] along with a more recently defined factor—maternal nutrition [5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Studies of maternal vitamin D status have examined cesarean delivery, and not instrumental delivery or prolonged labor. Findings are mixed, potentially due to varying definitions of cesarean including primary, 20 , 21 cause-specific, 21 , 22 emergency or elective, 23 , 24 and/or all cause. 20 , 24 , 25 Two US studies found an inverse relationship between maternal vitamin D status and risk of primary cesarean delivery, 21 , 25 while other studies observed no associations.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies examined the association between serum vitamin D and acute cesarean delivery, but they showed conflicting results. The first study demonstrated no association between a low level (<30 nmol/l) of vitamin D and the risk of an acute cesarean delivery in a Pakistani population [32]. However, the women included in that study were characterized by malnourishment in addition to their vitamin D deficiency; moreover, the clothing customarily worn by Pakistani women may predispose them to vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 88%